PEMBERDAYAAN KADER LANSIA DALAM PENERAPAN MANAJEMEN RESIKO JATUH PADA LANSIA DI DESA SEMBUNG - Prihandhani, IGAA Sherlyna; Bulan Trisna, Made Oktaviani (P3M Universitas Aisyiyah Surakarta, 2024)
Entering old age, a person will experience a condition of physical deterioration characterized by less clear hearing, worsening vision, decreased muscle strength resulting in slow movements, and disproportionate body movements. As a result of the physical changes of the elderly, resulting in impaired physical mobility that will limit the independence of the elderly in fulfilling daily activities and cause the risk of falling in the elderly. In Indonesia, the prevalence of injuries falls in the population over the age of 55 years reaches 49.4%, the age over 65 years and over 67.1% (Ministry of Health, RI, 2017). This training aims to reduce the risk of falls in the elderly. This training will be held face-to-face for one month in four meetings. The meeting consisted of pre-test assessment activities, lectures, video screenings, booklet distribution and post-test assessments. Previously, the team prepared and tested high risk management videos which were used as educational media in this training. The results of the study obtained increased knowledge of the risk of falling by elderly cadres with pre-test and post-test scores of 60 and 80. So that this circumcision is effectively carried out for cadres in the application of fall risk management Entering old age, a person will experience a condition of physical deterioration characterized by less clear hearing, worsening vision, decreased muscle strength resulting in slow movements, and disproportionate body movements. As a result of the physical changes of the elderly, resulting in impaired physical mobility that will limit the independence of the elderly in fulfilling daily activities and cause the risk of falling in the elderly. In Indonesia, the prevalence of injuries falls in the population over the age of 55 years reaches 49.4%, the age over 65 years and over 67.1% (Ministry of Health, RI, 2017). This training aims to reduce the risk of falls in the elderly. This training will be held face-to-face for one month in four meetings. The meeting consisted of pre-test assessment activities, lectures, video screenings, booklet distribution and post-test assessments. Previously, the team prepared and tested high risk management videos which were used as educational media in this training.The results of the study obtained increased knowledge of the risk of falling by elderly cadres with pre-test and post-test scores of 60 and 80. So that this circumcision is effectively carried out for cadres in the application of fall risk management. Keywords: Training, Elderly Cadres, Fall Risk Management